NEUROLOGICAL MANIFESTATIONS IN HIV-POSITIVE INMATES WITHIN AZERBAIJANI CORRECTIONAL FACILITIES - Abdullayeva, N.R. (World of Medicine and Biology, 2025)
A cross-sectional study recruited 376 incarcerated individuals from Azerbaijani penitentiary institutions, including 257 human immune deficiency virus (HIV)-positive (main group) and 119 HIV-negative participants (control group). Clinical, neurological, and psychological evaluations were conducted using standardized tools, adapted for the local context. The main group had shorter sentences, with 36.6 % serving ≤1 year, (14.3 % in the control group (p
Keywords: HIV; polyneuropathy; HIV-associated neurocognitive disorder; quality of life